Co-prescription of naloxone as a Universal Precautions model for patients on chronic opioid therapy—Observational study. Issue 4 (1st October 2016) - Takeda, Mikiko Y.; Katzman, Joanna G.; Dole, Ernest; Bennett, Melissa Heinz; Alchbli, Amal; Duhigg, Daniel; Yonas, Howard
ABSTRACT: Background: The epidemic of lethal prescription opioid overdose is one of the most pressing public health problems in the United States. In an ambulatory clinic setting, current practice guidelines suggest that health care providers should screen patient's aberrant drug-related behaviors. Given the difficulty of predicting which patients on chronic opioid therapy (COT) will experience opioid overdose, a new paradigm of harm reduction is called for. In previous studies, naloxone, an opioid antagonist, was given only to high-risk patients. However, if naloxone is co-prescribed in a Universal Precautions manner for all patients receiving COT, this may have a significant impact on intentional and unintentional opioid overdose deaths. Methods: Adult patients treated with COT for chronic noncancer pain are eligible study participants at the University of New Mexico Pain Center. The primary goal of this 1-year study was to develop an efficient Universal Precautions model for co-prescribing of naloxone with COT in the ambulatory clinic setting. Outcome measures included demographic data, detailed medical and substance use history, current morphine equivalent dose (MED), other "high-risk" medications used, and opioid misuse risk. Results: One hundred and sixty-four patients were enrolled in this study. All subjects were educated about the risks of opioid overdose and provided naloxone rescue kits. No overdoses occurred in the study population. Follow-up data illustrated that approximately 57% of the cohort had depressive disorder, the median MED was 90 mg/day, and the median Current Opioid Misuse Measure score (COMM) was 5.0. Conclusions: The ambulatory co-prescribing of naloxone in a Universal Precautions model for all patients prescribed COT can be adopted as a useful public health intervention. This study illustrates a model that can be used to educate patients, caregivers, and an interdisciplinary team of health care professionals in an academic medical center.